Metapolitical seduction: Women's language and white nationalism - Tebaldi, Catherine (Journal of Linguistic Anthropology, 2024)
This paper examines the enregisterment of white nationalist women's language as metapolitical seduction, in anti-feminist conversion videos designed both to seduce men and to restore them to their proper place—above women. First, the paper analyzes the metapragmatics of submissive femininity, then the characters this far right fairy tale invents, and finally how they come to represent a metapolitical order which aligns gender, nation, tradition, and language. Women's language contributes to the white nationalist metapolitical project of resurrecting white masculinity and re-gendering the world, also revealing mechanisms by which white supremacy is made to appear not only normal, but desirable.
Disponible en ligne à https://doi-org.proxy.bibliotheques.uqam.ca/10.1111/jola.12418
Keywords: 2000 à aujourd'hui; 2010-2019; antiféminisme; approches et analyses; cours; discipline; discours médiatique; histoire et politique; internet; lin2685; linguistique; premier cycle; périodes historiques; ressource en ligne; sciences humaines; système colonial; systèmes d'oppressions; thématiques; théorie critique de la race; trad wife